국내 디자인 분야 시지각 관련 실험연구의 방법론에 관한 메타분석 - 이현승; Hyun Seung Lee; 김일; 교신저자; Il Kim (기초조형학연구, 2015)
본 연구의 목적은 메타분석을 통한 국내 디자인분야의 시지각 관련 실험연구의 방법론적 측면의 경향 파악 및 향후 유사연구의 실험설계를 위한 기초자료제시에 있다. 실험연구를 다룬 메타분석에 있어 분석의 방법론적 측면을 파악하기 위해 실험연구를 다룬 메타분석 사례가 고찰된 결과, 구체적인 실험 경향과 결과의 분석을 위한 가이드라인이 설정되는 경향이 파악되었다. 본 연구에서는 국내의 108 편의 실험연구논문을 대상으로, 실험내용제시까지의 절차 및 피험자설계방법 등의 구체적 분석변수를 기준으로 한 메타분석이 수행되었으며, 결과는 다음과 같다, 첫째, 영상과 인터페이스디자인분야에서 2010 년대 들어 모바일 기술을 위한 연구 빈도가 상승하는 경향이, 제품과 의상디자인 등에서는 시각적선호도에 관한 연구 비율이 높은 경향이, 환경과 건축 등 공간을 다루는 분야에서는 일반적으로 3D 공간을 다룬 자극물이 3D 매체로서 제시되는 비율이 높은 경향을 보였다. 둘째, 실험물에 대한 지각자의 반응을 연구하는 사례에서는 노출시간과 측정방법에 소요시간이 짧은 실험설계가, 실험물 노출 이후의 기억을 다루는 유형의 경우 상대적으로 소요시간이 긴 설계가 적용되었다. 셋째, 각 연구별 실험물 노출과 제시방법의 차이가 있었으나 피험자내설계와 설문측정 방법이 가장 일반적으로 사용된 점으로 보아, 실험진행의 효율성이 중시된 것으로 보인다. 따라서 향후 관련연구에서는 실험진행의 효율성과 함께 실험결과에 영향을 미칠 수 있는 요인을 최소화할 수 있는 방법론적 측면 또한 고려되어야 할 것이다. The purpose of this study is to provide the research tendency of Visual Perception adapting Experiment as the research methodology in domestic design studies. To comprehend methodology of the meta-analysis dealing with ‘experiment researches’, existing cases were analyzed. As a result, it was found out that guidelines for specific analyzation were configured in the most cases. Regarding this, 108 of domestic articles on Visual Perception experiment searched and they were then meta-analyzed by specific criteria. The results of the meta-analysis are stated below. 1st, in 2010s, the researches for the mobile technology were increased in Motion graphic and Interface design, and the percentage of researches dealing with the visual-preference were higher in Product and Fashion, 3D experimental-objects and 3D presentation method were mainly adapted in Environment and Architecture. 2nd, experiments on the subjects`` re-action were designed consuming relatively short time on stimuli exposure and re-action measurement, and cases dealing with subjects`` memory consisted of processes consuming longer time. 3rd, although there were the differences on subject exposing and presenting methods in each, Within subject design and Survey were the most popular in subject and measurement design. Regarding this, it could be analyzes that the efficiency of experiment progresses was preferentially respected. Thus, in further researches, the efficiency and sophisticated experiment design are equally needed to minimize external effects affecting pure results of experiments.